NOx emissions in China: historical trends and future perspectives - B. Zhao; S. X. Wang; H. Liu; J. Y. Xu; K. Fu; Z. Klimont; J. M. Hao; K. B. He; J. Cofala; M. Amann (Atmospheric Chemistry and Physics, 2013)
Nitrogen oxides (NOx) are key pollutants for the improvement of ambient air quality. Within this study we estimated the historical NOx emissions in China for the period 1995–2010, and calculated future NOx emissions every five years until 2030 under six emission scenarios. Driven by the fast growth of energy consumption, we estimate the NOx emissions in China increased rapidly from 11.0 Mt in 1995 to 26.1 Mt in 2010. Power plants, industry and transportation were major sources of NOx emissions, accounting for 28.4%, 34.0%, and 25.4% of the total NOx emissions in 2010, respectively. Two energy scenarios, a business as usual scenario (BAU) and an alternative policy scenario (PC), were developed to project future energy consumption. In 2030, total energy consumption is projected to increase by 64% and 27% from 2010 level respectively. Three sets of end-of-pipe pollution control measures, including baseline, progressive, and stringent control case, were developed for each energy scenario, thereby constituting six emission scenarios. By 2030, the total NOx emissions are projected to increase (compared to 2010) by 36% in the baseline while policy cases result in reduction up to 61% in the most ambitious case with stringent control measures. More than a third of the reduction achieved by 2030 between least and most ambitious scenario comes from power sector, and more than half is distributed equally between industry and transportation sectors. Selective catalytic reduction dominates the NOx emission reductions in power plants, while life style changes, control measures for industrial boilers and cement production are major contributors to reductions in industry. Timely enforcement of legislation on heavy-duty vehicles would contribute significantly to NOx emission reductions. About 30% of the NOx emission reduction in 2020 and 40% of the NOx emission reduction in 2030 could be treated as the ancillary benefit of energy conservation. Sensitivity analysis was conducted to explore the impact of key factors on future emissions.